PENGARUH HAIR TONIC LIDAH MERTUA (Sanseviera Trifasciata Prain) dan SELEDRI (Apium Graveolens Linn)â€ Untuk MENGURANGI RAMBUT RONTOK - Nurjanah, Nurjanah; Krisnawati, Maria (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2014)
Penelitian bertujuan untuk mengetahui uji kesukaan hair tonic lidah mertua dan seledri yang meliputi warna, aroma, dan kesan pemakaian, mengetahui pengaruh hair tonic lidah mertua dan seledri untuk mengurangi rambut rontok. Penelitian eksperimen dengan objek penelitian hair tonic lidah mertua dan seledri. Jumlah sampel yang diambil 9 orang responden yang dikelompokkan menjadi 3 kelompok produk yaitu H1 (40ml:40ml), H2 (53ml:27ml), H3 (27ml:53ml). Analisis dataÂ menggunakan Anava Tunggal. Hasil analisis Anava sebelum pemakaian dan setelah membuktikan bahwa terdapat pengaruh diantara ketiga hair tonic setelah pemakaian menjadi berkurang setelah perawatan rambut rontok. Simpulan 1) hair tonic disukai adalah hair tonic lidah mertua dan seledri dengan proporsi 53ml:27 ml yang memiliki kriteria berwarna coklat muda dan tampak bening, beraroma khas menthol, khas lidah mertua dan khas seledri, dioleskan di kulit kepala tidak perih. 2) Ada pengaruh penggunaan ketiga komposisi hair tonic lidah mertua. Dari ketiga hair tonic, yang paling berpengaruh pada rambut rontok adalah hair tonic H3 (27ml:53ml) banyak seledri dibanding lidah mertua.The purpose of this study was to find the fondness test result of hair tonicsmade from sansevieria and celery, which consisted of color, scent, and the impression of its application. In addition, this study was implemented to find out the effect of sansevieria and celery hairtonics toward hair loss.The method of this study was experimental research, with sansevieria and celery hair tonic as the research objects. The samples which were taken from ninerespondents were classified into three groups: H1 (40ml: 40ml), H2 (53ml: 27ml), H3 (27ml: 53ml). The data analysis was done by using Single ANOVA. The ANOVA test prior and after the experiment showed that there were differences among the three hair tonics. The first conclusion (1), the most preferred hair tonic was sansevieria and celery hair tonic with 53 ml : 27 ml proportion, which has the criteria of light brown coloured, clear looking, has menthol scent (typical of sansevieria and celery), and not sore when applied on the head. The second conclusion (2), ANOVA results were increased based on the values retrieved prior and after the use of hair tonic, with an average H1value (40ml: 40ml) in which the average hair loss was reduced from 106 to 48 strands, H2 (53ml: 27ml) in which the average hair losswas reduced from 101 to 50 strands, and H3 (27ml: 53ml) in which the average hair loss was reduced from 102 to 54 strands. Of the three hair tonics, the most influential toward hair loss was H3 (27ml: 53ml) which has more portion of celery than sansevieria